How Robert Frost Made Realism Matter - Barron, Jonathan N. (Book collections on Project MUSE., 2015)
Robert Frost stood at the intersection of nineteenth-century romanticism and twentieth-century modernism and made both his own. Frost adapted the genteel values and techniques of nineteenth-century poetry, but Barron argues that it was his commitment to realism that gave him popular as well as scholarly appeal and created his enduring legacy. This highly researched consideration of Frost investigates early innovative poetry that was published in popular magazines from 1894 to 1915 and reveals a voice of dissent that anticipated "The New Poetry"--A voice that would come to dominate American poetry as few others have.